Aplikasi Konsep Ergonomi Pada Fasilitas Kerja Bakso Di Cakra Gajah Mungkur Cabang 1 Cipunagara - Prasetyo, Rezky Nur; , Indah Pratiwi, S.T., M.T; , Dr. Suranto, M.M (2015)
This research was conducted in the effort meatballs Chakra Elephant Mungkur Branch 1 Cipunagara, research conducted to test the level of occupational risk occurring at poduksi operator meatballs are done manually and conditions of employment are still modest facilities which give rise to many complaints of work on the part of the operator's body. The aim of this study is to perform repair work and relayout facility design work facilities to reduce the risk of complaints generated by production operators meatballs and produce tools according to the concept of ergonomics. Research carried out on ten production operators who serve research respondents. Methods of data collection was done by interview, observation, questionnaire NBM, literature. Benefits resulting research work posture complaints database in order to get repairs to the facility design work and relayout working facilities. The method used is the NBM (Nordic Body Map) to locate the type of complaint to the respondent by spreading kuisiomer NBM, JSI (Job Strain Index) measures the risk of working in the hand by making observations and calculations in the printing section incision, ARC (Activity Relationship Charts) see the closeness between working facilities, and anthropometry were used to carry out repair work facility design. The resulting output is generated from the data NBM many grievances felt by the operator which can lead to occupational risk, JSI Calculations show that the activity penecetakan and the incision is done manually at risk with JSI value> 7, application design improvements and working facilities can relayout reducing the risk of work and improve work performance printing production operator meatballs.